Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,260 questions

17,801 answers

1,438 comments

33,889 users

Prove ln(secθ + tanθ) + ln(secθ - tanθ) = 0?

0 votes
When secθ = 1/cosθ and tanθ = sinθ/cosθ
asked Dec 26, 2012 in TRIGONOMETRY by johnkelly Apprentice

2 Answers

0 votes

ln(secθ + tanθ) + ln(secθ - tanθ) = 0

First take left hand side

= ln(secθ + tanθ) + ln(secθ - tanθ)

= ln((secθ + tanθ)(secθ - tanθ))

= ln(sec^2θ - tan^θ)

= When secθ = 1/cosθ and tanθ = sinθ/cosθ

= ln(1/cosθ ^2θ -sin^2θ/cos^2θ)

= ln(1 -sin^2θ/ cos^2θ)

= ln(1 -sin^2θ/ cos^2θ)

Using trigonometric formula sin^2θ+cos^2θ=1

= ln(cos^2θ/ cos^2θ)

= ln(1)

= 0

ln(secθ + tanθ) + ln(secθ - tanθ) = 0

answered Dec 26, 2012 by ashokavf Scholar
0 votes

ln(secθ + tanθ) + ln(secθ - tanθ) = 0

First take left hand side

= ln(secθ + tanθ) + ln(secθ - tanθ)

= ln((secθ + tanθ)(secθ - tanθ))

= ln(sec^2θ - tan^2θ)

= When secθ = 1/cosθ and tanθ = sinθ/cosθ

= ln(1/cosθ ^2θ -sin^2θ/cos^2θ)

= ln(1 -sin^2θ)/( cos^2θ)

= ln(1 -sin^2θ/ cos^2θ)

Using trigonometric formula sin^2θ+cos^2θ=1

= ln(cos^2θ/ cos^2θ)

= ln(1)

= 0

ln(secθ + tanθ) + ln(secθ - tanθ) = 0

 

answered Dec 29, 2012 by krish Pupil

Related questions

asked Jan 22, 2015 in TRIGONOMETRY by anonymous
asked Nov 20, 2014 in TRIGONOMETRY by anonymous
asked Nov 13, 2014 in TRIGONOMETRY by anonymous
asked Oct 22, 2014 in TRIGONOMETRY by anonymous
...